What is the source of preschool children's memories of events from their own lives?. Issue 2 (20th January 2022) - Nicoladis, Elena; Svob, Connie; Smithson, Lisa
Abstract: In experimental tasks, preschool children sometimes mistakenly attribute memories to themselves rather than external sources, with decreasing source errors between 4‐ and 5‐years of age. In this research, we tested whether these developmental changes are also observed in spontaneously generated memories of personal life events. 4‐ and 5‐year olds generated life event memories and provided age estimates for when they took place. The children at both ages most often mentioned events that they could plausibly remember and some memories from external sources, including vicarious memories and events beyond their lifespan. Parents affirmed the accuracy of their children's memories and reported that some events were only told to or were imagined by the children. Our findings suggest that preschool children most often report events that they themselves remember and occasionally include events likely originating from external sources. These results add to the evidence showing that children's memories for events can be accurate.